Aplikasi Algoritma Kruskal dan Sollin Pada Jaringan Transmisi Nasional Provinsi Sulawesi Selatan - Kusnadi Kusnadi; Windu Gata; Fariszal Nova Arviantino (LPPM Universitas Mulia, 2022)
Graph theory is one part of the branch of mathematics that is now very famous in computer design. The substitution of a graph is an object statement referred to as a noktah, circle or point, and the object relationship is referred to as a line. Graph is applied in various scientific disciplines, for example: economics, genetic psychology, operation research and network optimization (telecommunication network, PLN transmission (electricity network, PDAM water distribution network). Kruskal and Sollin's algorithm have some similarities in their use for solving the problem of trees stretching the minimum from the smallest to the largest amount in each weight. In the article discussing the minimum range tree, especially kruskal and sollin algorithms, and applied more specifically to the national transmission network of South Sulawesi Province, then the network can be obtained optimally.